Dua Dunia Seni: Industri Kreatif Fesyen di Bandung dan Bali - Achwan, Rochman (UI Scholars Hub, 2014)
Many countries, including Indonesia, have paid attention to support the development of creative industry. Economic sociologists and sociologits of art have done researches on dynamics of this industry for quite sometime. By employing concepts of Art World and institutional (social) networks, this study attempts to answer two important questions. First, how do dynamics of social relationships within Art Worlds occur in an arena of fashion creative industries in Bandung and Bali? Second, to what extent local government plays roles in the drive of development of this industry in both areas? The main focus of this study is distro fashion industry in Bandung and Balinese fine clothing in Bali. Extended case method has been used to collect data from various actors. Fifty key informants in each area have been interviewed. This study reveals that the Art Worlds of fashion industries in both areas need to re-invent themselves so that they are capable of inovating their methods of production and distribution. Moreover, local governments need to facilitate a constructive development of social networks among fashion producers. The future of creative fashion industry will depend on the maturity of social networks that signified by innovative cooperation between local governments and societies of fashion industries.